Perancangan Pembangkit Listrik Tenaga Surya (PLTS) Sebagai Sumber Energi Listrik Untuk Akuaponik - Yudi Chandra (entries, 2022)
The higher the growth rate, the greater the need for electrical energy required. In addition, the increase in population has resulted in many land functions becoming non-agricultural or agricultural from non-agricultural land. Therefore, the way to overcome the shortage of food security and environmentally friendly is the aquaponics system. Aquaponics cannot be separated from air circulation, where this water is the main need for both fish and plants. The water pump is an air propulsion driven by electrical energy. The problem is, because the air used for both plants and fish is the main ingredient, the water must flow and if the electricity goes out or other disturbances in electricity, the air flow process will stop, in addition to reducing electrical energy from PLN, one of the efforts that can be done This is done by utilizing alternative energy, namely using solar light energy into electrical energy or called PLTS. In the design of this PLTS using an off grid system. This off grid system is intended as a substitute for electricity when the electricity source from PLN is off or there is no PLN electricity at all. The design of this PLTS is done by calculating the required PLTS components, after that determining where to put the solar panels that are used. After knowing the specifications of the components, then you can do calculations for the Budget Plan (RAB) which will be recommended in the design of PLTS with this off grid system. The results of this PLTS design with an off grid system are using components in the form of solar panels, solar charge controllers, batteries and inverters. After calculating the load on aquaponics, in this design the components are obtained, namely 1 solar panel with a capacity of 150 Wp, 1 battery with a capacity of 70 Ah 12 Volt, 1 inverter with a capacity of 500 watts and 1 SCC capacity of 10 A. . The recommended fee is Rp. 3.500.000.00., for the PLTS.